Adsorption properties of acetylene, ethylene and ethane in UiO-66 with linker defects and NO2 functionalization. Issue 1 (17th December 2020) - Pandey, H.; Barrett, T.; Gross, M. D.; Thonhauser, T.
Abstract : Using calorimetry and ab initio simulations, we uncover atomic-level details of the loading/separation process of C2 hydrocarbons in UiO-66. Abstract : Separation of small hydrocarbon gases is crucial for many industrial processes, but the high energy demand of current separation techniques encourages exploration of alternative sorption-based approaches. Here, we investigate the metal organic framework UiO-66(Zr) as possible solid adsorbent with a focus on the fundamental sorption mechanisms of C2 hydrocarbons in the presence of linker defects and NO2 functionalization. To this end, we directly measure heats of adsorption with calorimetry and correlate our results with ab initio calculations. In particular, we study adsorption of C2 H2, C2 H4 and C2 H6 at 293 K and 195 K. At 293 K, the measured low-coverage enthalpy is found to be an average enthalpy of multiple adsorption sites. However, at 195 K, the low-coverage enthalpy corresponded to the strongest binding site, i.e. the linker defect site. We find that C2 H2 exhibits the highest adsorption enthalpy with a significant gap of ∼6 kJ mol −1 to C2 H4 and ∼9 kJ mol −1 to C2 H6 . Our ab initio calculations show excellent agreement with our experiments and are crucial to uncover the mechanisms that lead to the observed differences in binding affinity as a function of coverage. We also find that binding enthalpies increase for all three gases by adding –NO2 functional groups, which even further increase the gap to ∼9 kJ mol −1 and ∼10 kJ mol −1 for C2 H4 and C2 H6, respectively. Our findings provide mechanistic insight that suggests that linker defects in UiO-66(Zr) have promise to improve its effectiveness as a solid adsorbent in C2 H2, C2 H4 and C2 H6 applications and that functionalization may be used to increase specificity.